Injustice at Work and Leukocyte Glucocorticoid Sensitivity. Issue 5 (June 2015) - Herr, Raphael M.; Loerbroks, Adrian; van Vianen, Annelies E.M.; Hoffmann, Kristina; Fischer, Joachim E.; Bosch, Jos A.
ABSTRACT Objective Organizational justice refers to perceived fairness at the workplace. Low organizational justice has been identified as a major source of distress and a predictor of poor health. Impaired regulation of immunological and inflammatory pathways may, in part, underlie these health effects. The present study investigated the association of organizational justice with leukocyte glucocorticoid sensitivity in vivo. Methods Organizational justice was assessed among 541 male factory workers (mean [standard deviation] age = 46 [9] years) by questionnaire. Cortisol release was measured at three time points before blood collection and summed as the area under the curve. Blood was used to assess leukocyte (white blood cell [WBC] count) subsets (neutrophils [%WBC], lymphocytes [%WBC], and the neutrophil/lymphocyte ratio). Glucocorticoid sensitivity was operationalized as the correlation between cortisol release and these hematologic parameters. Associations were adjusted for demographics, work characteristics, and life-style variables. Results A dose-response relationship between organizational justice and glucocorticoid sensitivity was found. Cortisol and hematologic parameters showed the expected significant association among individuals reporting high (all β values ≥ |.26|; all p values ⩽.001) or medium organizational justice (all β values ≥ |.15|; all p values ⩽.050), but not among those reporting low organizational justice (all β values ⩽ |.04|; all p values > .10). These regression slopes differed significantly between organizational justice groups (p values for interaction < .050). Conclusions Low justice at work is associated with an impaired ability of endogenous cortisol to regulate leukocyte distribution in vivo. These findings identify a novel biological pathway by which organizational justice may affect health.